Application-based Framework for Analysis, Monitoring and Evaluation of National Open Data Portals - Raca, Vigan; Velinov, Goran; Cico, Betim; Kon-Popovska, Margita (Science and Information (SAI) Organization Limited, 2021)
Open Government Data (OGD) portals are considered of significant national importance towards transparency and accountability improvement. The continuous publication of data in OGD portals introduces the need for highquality data and the qualitative portal itself. This paper aims to address the data quality issues through a framework composed of several components aimed at measuring and monitoring the OGD portals in an automated way. Through this proposed framework, is intended to monitor and evaluate OGD quality, respectively OGD portals, and to show their progress/regress based on accumulated scores for different periods. The advantage of the proposed framework is the compatibility with any OGD Portal due to its flexibility of integration. The integration interface consists of only a few basic metrics but is necessary that almost the OGD portal possesses and can produce very compressive results. The other advantage is the possibility of extraction of collected data for further analysis and the introduction of artificial intelligence (AI) for prediction purposes to point out how the OGD portals will stand in the next period.
Keywords: Open data; government; datasets; evaluation; portals; framework